2018
DOI: 10.3390/catal8070280
|View full text |Cite
|
Sign up to set email alerts
|

PdO/ZnO@mSiO2 Hybrid Nanocatalyst for Reduction of Nitroarenes

Abstract: Development of a novel approach for synthesizing nanostructured catalysts and achieving further improvements in catalytic activity, effectiveness, and efficiency remains a major challenge. In this report, we describe the preparation of a nanostructured PdO/ZnO@mSiO 2 hybrid nanocatalyst featuring well-dispersed PdO nanoparticles within hollow ZnO@mSiO 2 . The as-prepared PdO/ZnO@mSiO 2 hybrid nanocatalyst exhibited good morphological features, derived from the controlled stepwise synthesis from Pd/PS@ZIF-8@mSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…20 Very recently, our group reported the reduction of nitroarenes by PdO/ZnO@mSiO 2 hybrid nanocatalysts. 21 Xu et al emphasized on the photocatalytic degradation of 4-chlorophenol by Ag/AgBr/TiO 2 / GO. 22 Cui et al reported on the facile preparation of silver halide nanoparticles on visible light photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…20 Very recently, our group reported the reduction of nitroarenes by PdO/ZnO@mSiO 2 hybrid nanocatalysts. 21 Xu et al emphasized on the photocatalytic degradation of 4-chlorophenol by Ag/AgBr/TiO 2 / GO. 22 Cui et al reported on the facile preparation of silver halide nanoparticles on visible light photocatalysts.…”
Section: Introductionmentioning
confidence: 99%